Occurrence of glutathione in bacteria. - Fahey, R C (1978)
Glutathione and soluble thiol content were examined in a broad spectrum of bacteria. Significant soluble thiol was present in all cases. The thiol compound was glutathione in most of the gram-negative bacteria but not in most of the gram-positive bacteria studied. Glutathione was absent in four anerobes and one microaerophile but was present in a blue-green bacterium. The glutathione content of Escherichia coli increased significantly during transition from exponential to stationary phase.